Antibiotic resistance characterization, virulence factors and molecular characteristics of Bacillus species isolated from probiotic preparations in China - Xin Jin; Ling Zhang; Yu Cao; Zhen Dai; Xiaoming Ge; Rui Cai; Ruirong Wang; Ziyan Hu (Journal of Global Antimicrobial Resistance, 2025)
Objectives: The aim of this study was to determine the phenotypic and molecular characteristics of antibiotic-resistant Bacillus spp. isolated from probiotic preparations in China. Methods: Bacillus strains were isolated from probiotic preparations and then identified using 16S rDNA sequencing. Drug sensitivity tests were conducted to determine their susceptibility to seven antibiotics. Whole genome sequencing was performed on the most resistant strains, followed by analysis of their molecular characteristics, resistance genes and virulence factors. Results: In total, we isolated 21 suspected Bacillus species from seven compound probiotics, which were identified by 16S rDNA as 12 Bacillus licheniformis, six Bacillus subtilis and three Bacillus cereus. The determination of antimicrobial susceptibility showed widespread resistance to chloramphenicol (95.2%), erythromycin (85.7%) and gentamicin (42.9%). Whole genome sequencing of seven resistant strains revealed that J-6-A (Bacillus subtilis) and J-7-A (Bacillus cereus) contained a plasmid. The resistance gene analysis revealed that each strain contained more than ten resistance genes, among which J-7-A was the most. The streptomycin resistance gene strA was detected in all strains. The chloramphenicol resistance genes ykkC and ykkD were found in J-1-A to J-5-A and were first reported in Bacillus subtilis. The erythrocin resistance gene ermD was detected in strains J-1-A to J-4-A. There were also more than 15 virulence factors and gene islands (GIs) involved in each strain. Conclusions: These results confirm the potential safety risks of probiotics and remind us to carefully select probiotic preparations containing strains of Bacillus species, especially Bacillus cereus, to avoid the potential spread of resistance and pathogenicity.